2020
DOI: 10.3389/fphar.2020.01021
|View full text |Cite
|
Sign up to set email alerts
|

Turmeric and Its Major Compound Curcumin on Health: Bioactive Effects and Safety Profiles for Food, Pharmaceutical, Biotechnological and Medicinal Applications

Abstract: Curcumin, a yellow polyphenolic pigment from the Curcuma longa L. (turmeric) rhizome, has been used for centuries for culinary and food coloring purposes, and as an ingredient for various medicinal preparations, widely used in Ayurveda and Chinese medicine. In recent decades, their biological activities have been extensively studied. Thus, this review aims to offer an in-depth discussion of curcumin applications for food and biotechnological industries, and on health promotion and disease prevention, with part… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
348
1
6

Year Published

2020
2020
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 534 publications
(356 citation statements)
references
References 202 publications
(308 reference statements)
1
348
1
6
Order By: Relevance
“…Curcumin, the main curcuminoid in Curcuma longa L. (turmeric), is a low-molecular-weight polyphenol, widely used in Ayurveda and Chinese medicine [ 87 ]. Turmeric type 97 (77% curcumin, 17% dexethoxycurcumin, and 3% bisdemethoxy curcumin) induced an increase in the level of transferrin receptor 1 (TfR1) and the induction of activated iron-regulatory proteins (IRPs), a decrease of the hepatic ferritin level and its H and L subunits [ 88 ].…”
Section: Natural Antioxidants In Iron Overload Treatmentmentioning
confidence: 99%
“…Curcumin, the main curcuminoid in Curcuma longa L. (turmeric), is a low-molecular-weight polyphenol, widely used in Ayurveda and Chinese medicine [ 87 ]. Turmeric type 97 (77% curcumin, 17% dexethoxycurcumin, and 3% bisdemethoxy curcumin) induced an increase in the level of transferrin receptor 1 (TfR1) and the induction of activated iron-regulatory proteins (IRPs), a decrease of the hepatic ferritin level and its H and L subunits [ 88 ].…”
Section: Natural Antioxidants In Iron Overload Treatmentmentioning
confidence: 99%
“…Modern medicine has shown that curcumin exhibits a broad range of biological and pharmacological activities, including antioxidant [ 20 ], anti-inflammatory [ 21 ], anti-tumor and chemosensitizing [ 22 ], hepatoprotective [ 23 ], lipid-modifying [ 24 ] and neuroprotective [ 25 ] effects and are suggested to improve mental illnesses due to its ability to modulate numerous signaling molecules [ 8 , 26 , 27 ]. Many studies show that it is safe to consume 8 g per day of curcumin [ 28 , 29 ]. Therefore, many curcumin based products are available such as tablets, capsules, and as an additive to various energy drinks [ 27 ].…”
Section: Curcuminmentioning
confidence: 99%
“…Important biotechnological applications of curcumin are widely used in the food industry where it is used as a spice or food additive, at a dose of 5–500 mg/kg, to ameliorate foodstuffs’ palatability and storage stability. The European Union has authorized the use of curcumin as food color with the name of CI 75300, Natural Yellow 3 or diferuloylmethane, and with the E100 code [ 20 ]. Curcumin is an efficient food preservative in its ability to suppress lipid peroxidation, suggesting a role as a possible natural preservative [ 21 ].…”
Section: Bioactivity and Health Benefits Of Curcuminmentioning
confidence: 99%